Expression Profile of Glossina pallidipes MicroRNAs During Symptomatic and Asymptomatic Infection With Glossina pallidipes Salivary Gland Hypertrophy Virus (Hytrosavirus) - Meki, Irene K.; İnce, İkbal A.; Kariithi, Henry M.; Boucias, Drion G.; Ozcan, Orhan; Parker, Andrew G.; Vlak, Just M.; van Oers, Monique M.; Abd-Alla, Adly M. M. (Frontiers in Microbiology, 2018)
The Glossina pallidipes salivary gland hypertrophy virus (GpSGHV) infects tsetse flies asymptomatically or symptomatically. Symptomatic infections cause reproductive dysfunctions and colony collapse which hinder tsetse control via sterile insect technique (SIT). Here, small RNAs were sequenced and profiles in asymptomatically and symptomatically infected G. pallidipes flies determined. Thirty host-encoded microRNAs (miRNAs) were present in both the asymptomatic and symptomatic fly profiles, while 14 host miRNAs were expressed specifically in asymptomatic flies versus seven in symptomatic flies. Of the 30 shared miRNAs, 14 were differentially expressed when comparing asymptomatic with symptomatic flies. The most up-regulated host miRNAs in symptomatic flies was predicted to target immune-related mRNAs of the host. Six GpSGHV-encoded miRNAs were identified, of which five of them were only in symptomatic flies. These virus-encoded miRNAs may not only target host immune genes but may also participate in viral immune evasion. This evidence of differential host miRNA profile in Glossina in symptomatic flies advances our understanding of the GpSGHV-Glossina interactions and provides potential new avenues, for instance by utilization of particular miRNA to better manage GpSGHV infections in tsetse mass-rearing facilities, a prerequisite for successful SIT implementation.